Prevalence and characteristics Of miopia in elementary school children in Badung District , 2018 - WATU, THEDIUS; Handayani, Ariesanti Tri; Manuaba, Putra (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesRefractive disorders are the second most common cause of blindness at all ages after cataracts andare the leading cause of visual impairment in the world. The World The most common refractivedisorder in students especially in Asia is miopia. This study aims to determine the prevalence andcharacteristics of miopia in elementary school children in Badung Regency, Bali. MethodsThis research is an observational with analytic cross-sectional study approach. Data were collectedprospectively in children in four elementary schools in Badung, Bali. To assess the relationshipbetween sex, age, history of wearing glasses in parents and duration of near work activity withmyopia using chi-square. ResultsThe subjects were 1,067 students, consisting of 557 (52.2%) women and 510 (47.8%) men, the mostage was 9 years (19.1%), the average duration of near work activity was 83.79 ± 29, 46 hours/week,152 students (14.24%) with refractive disorders and bilateral myopia were the most refractivedisorders (65.8%). Of the 150 students with miopia, 60% were female students, aged at most 11years (28%), 90% of students had uncorrectedmiopia, 68% of parents of students without miopia,mean near work activity was 81,71±23,30 hours / week. No significant relationship was foundbetween sex and age and the prevalence of myopia. Significant relationship was found between theuse of glasses in parents and the length of close-up activity with myopia with PR=7.35 (95% CI:7.10-10.56) and PR=1.177 (95% CI 1.05-1.78). ConclusionThere are differences in the characteristics of miopia in primary school students between urban andremote areas and between developed and developing countries due to sociodemographicdifferences, level of education, type of activity, income and culture.